2013
DOI: 10.1007/s00595-013-0524-6
|View full text |Cite
|
Sign up to set email alerts
|

Infradiaphragmatic malperfusion of acute aortic dissection associated with previous abdominal aortic aneurysm repair

Abstract: Previous AAA graft replacement is a risk factor for infradiaphragmatic malperfusion in patients with acute aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Increased awareness of this complication, and the availability of better diagnostic tools, may improve the survival rates of patients with visceral ischemia. Ito and colleagues concluded that previous abdominal aortic aneurysm graft replacement was a risk factor for infradiaphragmatic malperfusion in patients with acute aortic dissection . Diagnostic procedures include CT, ultrasound, and laparoscopy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased awareness of this complication, and the availability of better diagnostic tools, may improve the survival rates of patients with visceral ischemia. Ito and colleagues concluded that previous abdominal aortic aneurysm graft replacement was a risk factor for infradiaphragmatic malperfusion in patients with acute aortic dissection . Diagnostic procedures include CT, ultrasound, and laparoscopy .…”
Section: Discussionmentioning
confidence: 99%
“…Ito and colleagues concluded that previous abdominal aortic aneurysm graft replacement was a risk factor for infradiaphragmatic malperfusion in patients with acute aortic dissection . Diagnostic procedures include CT, ultrasound, and laparoscopy . Organ ischemia owing to aortic dissection often requires emergency surgery for rapid restoration of blood flow to the true lumen.…”
Section: Discussionmentioning
confidence: 99%